Synthesis, spectroscopic characterization, and DFT analysis of dichlorido(η6-p-cymene)ruthenium(II) complexes with isonicotinate-polyethylene glycol ester ligands - Eichhorn Thomas; Dimić Dušan; Marković Zoran; Kaluđerović Goran N. (Journal of the Serbian Chemical Society, 2023)
Ruthenium complexes have gained significant attention due to the ruthenium similarity to iron, lower toxicity, and higher anticancer effectiveness than other compounds. In this contribution, five new isonicotinate-polyethylene glycol ester ligands were synthesised and characterised by NMR and IR spectroscopies. The corresponding Ru(II) complexes were also obtained, and their structure was investigated by traditional methods. The optimisation of structures was performed at B3LYP/6-31+G(d,p) level of theory for H, C, N and O atoms and B3LYP/LanL2DZ for Ru. The intramolecular stabilisation interactions were assessed through the natural bond orbital approach. The NMR chemical shifts were predicted by the gauge independent atomic orbital method and compared to the experimental values. High correlation coefficients and low mean absolute errors between these data sets proved that the predicted structures described well the experimental ones. The theoretical and experimental IR spectra were also compared, and differences in the most notable bands were described. One of the ligands (L5) and complexes (5) showed fluorescent properties due to methylisatoic moiety. The electronic spectra of this compound were modelled by the time dependent-density functional theory method. The difference of 11 nm between the experimental and the theoretical wavelength was explained by the interactions between the solvent and the solute. Further biological and theoretical studies are advised for this series of compounds.